(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Rowotamtu Village is one of the villages in Jember Regency that is the center of the tofu industry. Problems in waste treatment are the main issue that causes environmental pollution due to the lack of information related to processing tofu waste that can have economic value. This service and socialization activity aims to provide education and information about processing solid and liquid tofu waste into Liquid Organic Fertilizer (POC) and Tofu Dregs Crackers. This step is expected to reduce the negative impact of tofu waste that is not processed further. The results of the socialization and education showed a high level of participatory enthusiasm from the community to implement the knowledge they gained from the socialization to be applied directly in the snack industry and community agriculture. The evaluation of the activity showed that 100% of the community knew how to process tofu waste into POC and crackers, 95.2% had skills in making POC and crackers, 81% were interested in developing POC and cracker businesses, and 71.4% were interested in making products up to the certification stage. — Desa Rowotamtu merupakan salah satu desa di Kabupaten Jember yang menjadi pusat sentra industri tahu. Permasalahan dalam pengolahan limbah menjadi isu utama yang menyebabkan pencemaran lingkungan akibat kurangnya informasi terkait pengolahan limbah tahu yang dapat memiliki nilai ekonomis. Tujuan kegiatan pengabdian dan sosialisasi ini adalah memberikan edukasi dan informasi mengenai pengolahan limbah padat dan cair tahu menjadi Pupuk Organik Cair (POC) dan Kerupuk Ampas Tahu. Langkah ini diharapkan dapat mengurangi dampak negatif dari limbah tahu yang tidak diproses lebih lanjut. Hasil dari sosialisasi dan edukasi menunjukkan tingkat antusiasme partisipatif yang tinggi masyarakat untuk mengimplementasikan hasil pengetahuan yang mereka dapat dari sosialisasi untuk diterapkan secara langsung dalam industri makanan ringan dan pertanian masyarakat. Evaluasi kegiatan menunjukkan bahwa 100% masyarakat memiliki pengetahuan tentang cara pengolahan limbah tahu menjadi POC dan kerupuk, 95,2% memiliki keterampilan dalam pembuatan POC dan kerupuk, 81% berminat untuk mengembangkan usaha POC dan kerupuk, dan 71,4% berminat untuk membuat produk hingga tahap sertifikasi.